Risk factors and molecular epidemiology of fecal carriage of carbapenem resistant Enterobacteriaceae in patients with liver disease - Fangbing Tian; Yin Li; Yue Wang; Bing Yu; Jianxin Song; Qin Ning; Cui Jian; Ming Ni (BMC, 2023)
Abstract Background Carbapenem resistant Enterobacteriaceae (CRE) colonization is a risk factor for CRE infection. CRE infection results in an increase in mortality in patients with cirrhosis. However, minimal data regarding the prevalence and the risk factors of CRE colonization in patients with liver disease yet without liver transplantation are available. The present study aimed to investigate the prevalence, risk factors and molecular epidemiology characteristics of CRE fecal carriage among patients with liver disease. Methods Stool specimens from 574 adult inpatients with liver disease were collected from December 2020 to April 2021. CRE were screened using selective chromogenic agar medium and identified by the Matrix-Assisted Laser Desorption/Ionization Time-of-Flight Mass Spectrometry (MALDI-TOF MS). Antimicrobial susceptibility was determined using the broth microdilution method. Carbapenemase genes were characterized by polymerase chain reaction (PCR) and DNA sequencing. Multilocus sequence typing (MLST) was performed for Carbapenem Resistant Klebsiella pneumoniae (CR-KPN) isolates and Carbapenem Resistant Escherichia Coli (CR-ECO) isolates. Results The total number of stool specimens (732) were collected from 574 patients with liver disease. 43 non-duplicated CRE strains were isolated from 39 patients with a carriage rate of 6.79% (39/574). The carriage rate was 15.60% (17/109) in patients with acute-on-chronic liver failure (ACLF). Multivariate analysis indicated that ACLF (P = 0.018), the history of pulmonary infection within past 3 months (P = 0.001) and the use of third generation cephalosporin/β-lactamases inhibitor within past 3 months (P = 0.000) were independent risk factors of CRE colonization in patients with liver disease. Klebsiella Pnuemoniae (KPN) (51.28%) and Escherichia coli (ECO) (30.77%) were main strains in these patients. All CRE strains showed high resistance to most antimicrobials except for polymyxin B and tigecycline. Most (83.72%, 36/43) of the CRE carried carbapenemase genes. bla KPC-2 was the major carbapenemase gene. The molecular epidemiology of KPN were dominated by ST11, while the STs of ECO were scattered. Conclusions The present study revealed that CRE fecal carriage rates were higher in patients with ACLF than in patients without liver failure. ACLF, the history of pulmonary infection within past 3 months and the use of third generation cephalosporin/β-lactamases inhibitor within past 3 months were independent risk factors of CRE colonization in patients with liver disease. Regular CRE screening for hospitalized patients with liver disease should be conducted to limit the spread of CRE strain.